The Influence of Financial Technology and Influencer Marketing on Beauty Product Brand Awareness at the Sociolla.id Store in Center Point Medan - Jesslyn Calista; Pesta Gultom (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
The beauty sector demonstrates ongoing expansion and ingenuity annually. The beauty industry is presently expanding rapidly, with a steady influx of new brands emerging and evolving; beauty products within Indonesia encounter rivalry not just from local companies but also from global entities. Sociolla. id exists to offer an easier way for Indonesian consumers to acquire beauty products, but it faces difficulties due to insufficient financial technology services that could benefit customers and a need for more modern marketing tactics, like influencer marketing. This research focused on Sociolla. id customers, utilizing a sample size of 110 individuals. The findings reveal that financial technology has some effect on how well people know the Sociolla. id brand. The research also found that influencer marketing has a partial impact on how well people know the Sociolla. id brand. The study's data indicates that financial technology has a combined impact on the recognition of the Sociolla. id brand. The R Square (R2) statistic, or coefficient of determination, indicates that financial technology and influencer marketing together account for 79.7% of the variability, while the remaining 21.3% is impacted by other variables not included in the research model, such as cost, product attributes, and perceived worth.